EFFECT OF EMPLOYEE SATISFACTION AND EMPLOYEE DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. MEDIATECH CENTRA FILTER SURABAYA - Farah Jihan Nabilah; Sulastri Irbayuni (Jurnal Bisnis dan Keuangan, 2022)
This study aims to analyze the gain of progress and achieve goals. Companies need to encourage and monitor employee performance to develop their abilities to the potential. This research is quantitative, with the data used being secondary. The decline in the performance of employees in the production department has an impact on the company because it can hinder the company's filter production, and the company's production targets are not achieved. Human resource management's scope generally discusses human beings' matters, including employee job satisfaction. Employee job satisfaction is a factor that is considered necessary because it can affect the running of the company as a whole. The satisfaction felt by employees at work indicates that employees have feelings of pleasure in carrying out work duties. Job satisfaction is also a positive attitude of employees towards various situations in the workplace. For organizations, employee job satisfaction must receive attention and fulfilment of this is primarily the task of organizational leaders. For employees, job satisfaction is an individual factor, and a means to achieve work productivity. So within the scope of human resource management, job satisfaction factors benefit organizations/companies, employees, and even the community.